2010
DOI: 10.1108/02756661011036718
|View full text |Cite
|
Sign up to set email alerts
|

Making consultants earn their keep

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/ authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…For instance, a research of enterprise resource planning (ERP) system implementation projects found that external consultants are involved in 83% of the ERP implementation projects (Kumar et al, 2003). Furthermore, consulting services can represent a major cost for organizations (Jackson, 2010;Ehie and Madsen, 2005;Vogl, 1999;Mitchell, 1994;Baker and Faulkner, 1991). For example, Kumar et al (2003) point out that the consulting expenses may account for as much as 70% of the entire ERP implementation project costs.…”
Section: Problem Statementmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, a research of enterprise resource planning (ERP) system implementation projects found that external consultants are involved in 83% of the ERP implementation projects (Kumar et al, 2003). Furthermore, consulting services can represent a major cost for organizations (Jackson, 2010;Ehie and Madsen, 2005;Vogl, 1999;Mitchell, 1994;Baker and Faulkner, 1991). For example, Kumar et al (2003) point out that the consulting expenses may account for as much as 70% of the entire ERP implementation project costs.…”
Section: Problem Statementmentioning
confidence: 99%
“…Moderate Strong (Jackson, 2010;Kubr, 1993;Aje, 1988) PAYMENT CONTROL: Payment should be linked to performance.…”
Section: Strong Strongmentioning
confidence: 99%
See 3 more Smart Citations